Simulation of Conditions of Solid Fossil Fuels Formation for Underground Conversion Investigation; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Martemyanov S. M. Sergey Mikhailovich; Bukharkin A. A. Andrey Andreevich; Koryashov I. A. Iliya Aleksandrovich; Kvashnina O. S. Olga Sergeevna (Numerical Simulation of Physical and Chemical Processes, 2016)
Title screen